ENHANCING INSTITUTIONAL IMAGE IN HIGHER EDUCATION: THE ROLE OF SERVICE, EDUCATIONAL, AND INFORMATION QUALITY - Muchammad Ibnu Muzakir; Rokimin Rokimin; Sofwan Manaf; Nesa Novrizal (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study explores the influence of information quality, service quality, and perceived educational quality on the institutional image of Darunnajah University. The research employs a quantitative approach using a survey method involving students, lecturers, alumni, and administrative staff as respondents. Data were collected through questionnaires that had been tested for validity and reliability, and were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to examine the relationships among variables. The results indicate that perceived educational quality has the strongest influence on institutional image, followed by service quality and information quality. The research model explains 57.18% of the variance in institutional image, indicating that these three variables make a significant contribution to building the image of the university. The findings highlight the importance of integrating educational quality, service quality, and information quality in strengthening institutional reputation. Improving academic quality supported by professional services and the provision of accurate and transparent information can enhance public trust in the institution.